2006
DOI: 10.1080/02652030500415660
|View full text |Cite
|
Sign up to set email alerts
|

Migration of formaldehyde and melamine monomers from kitchen- and tableware made of melamine plastic

Abstract: . Migration of formaldehyde and melamine monomers from kitchen-and tableware made of melamine plastic. Food Additives and Contaminants, 2006, 23 (09) 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 The results indicated that continuous migration of formaldehyde and melamine takes place during the lifetime of these articles. The mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(70 citation statements)
references
References 7 publications
1
67
2
Order By: Relevance
“…There are studies in Shanghai, Taiwan, Hong Kong and other places reporting the significant association of lung cancer in women with expose to cooking oil fume (Zhong et al, 1999;Ko et al, 2000;Yu et al, 2006;Pan et al, 2008). Previous studies have shown that sugar, proteins, fat and amino acids can release some harmful substances, such as particulate matter (PM), polycyclic aromatic hydrocarbons, aromatic amines, nitro-PAHs, and aldehydes under the hightemperature treatment (Vainiotalo et al, 1993;Li et al, 1994;Wu et al, 1998;Chiang et al, 1999;Lund et al, 2006). Laboratory studies have demonstrated that cooking oil fumes condensates can induce DNA damages and oxidative stress in lung epithelial cells (Tung et al, 2001;Wu et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…There are studies in Shanghai, Taiwan, Hong Kong and other places reporting the significant association of lung cancer in women with expose to cooking oil fume (Zhong et al, 1999;Ko et al, 2000;Yu et al, 2006;Pan et al, 2008). Previous studies have shown that sugar, proteins, fat and amino acids can release some harmful substances, such as particulate matter (PM), polycyclic aromatic hydrocarbons, aromatic amines, nitro-PAHs, and aldehydes under the hightemperature treatment (Vainiotalo et al, 1993;Li et al, 1994;Wu et al, 1998;Chiang et al, 1999;Lund et al, 2006). Laboratory studies have demonstrated that cooking oil fumes condensates can induce DNA damages and oxidative stress in lung epithelial cells (Tung et al, 2001;Wu et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The degradation of sugar, the pyrolysis of proteins and amino acids, and the degradation of fat during the high-temperature treatment of food can generate harmful degradation products (13), such as particulate matter (PM), polycyclic aromatic hydrocarbons (PAH; ref. 2), aromatic amines (9), nitroPAHs (2,5), and aldehydes (13,14). Traditional Chinese cooking includes stir-frying and deep-frying, which generate significant amounts of COFs (15).…”
Section: Introductionmentioning
confidence: 99%
“…In these food safety incidents, melamine or related compounds were added to protein ingredients, foods, or animal feed, and thereby incorporated into a variety of animal and human foods 1) . Detection of this problem prompted massive recalls of human foods, pet foods, and livestock feed, resulting in huge economic losses.…”
Section: Introductionmentioning
confidence: 99%
“…Melamine or cyanuric acid was intentionally added to food ingredients to boost protein content since both melamine and cyanuric acid are rich in nitrogen 3) . Melamine and cyanuric acid can form extremely insoluble "spoke-like" crystals, which formed in human and animal kidneys and were suspected of compromising kidney function, leading to acute renal failure [1][2][3][4][5][6]. Melamine contamination in foods could reach a stunning level of 2563 ppm 4) .…”
Section: Introductionmentioning
confidence: 99%